Системне та творче мислення в професії розробника комп’ютерних ігор та персонажів - Базарна, П. А. (ХНУРЕ, 2024)
The profession of developer computer games and game characters is extremely creative and technically challenging. Systematic and creative thinking are such skills that can significantly affect the professional success of developers of computer games and game characters. Mastering the skills of systemic and creative thinking is part of the development of professional competence in the field of creating computer games and characters. The development of systemic and creative thinking are interrelated processes.
Keywords: творче мислення; персонаж